Segmented Reporting Analysis Pada Anandia Bakery - Rahayu, Resi; Putra Ananto, Rangga; Frima, Rini (Jurusan Akuntansi Politeknik Negeri Padang, 2016)
Companies need to know the profit contribution generated by each marketing area owned. To know the profit contribution of each marketing area, it is necessary to create income statement with segmented reporting approach (segmented reporting) each marketing area. Segmented reporting contains information about the amount of sales and certain the costs each marketing area. The purpose of this study is to determine the profit contribution generated by each marketing area in Anandia Bakery April 2017. This study uses variable costing method, which is useful to determine the cost of production just based on variable costs. The results of this study stated that all marketing areas owned by Anandia Bakery in April of 2017 are profitable. It can evidenced by the percentage of segment margin ratio for each large marketing area, it is above 40%. When the result of margin ratio more larger, the profit contribution that given by the marketing area is getting better.